HUBUNGAN PENGETAHUAN GIZI SEIMBANG DENGAN PRAKTIK GIZI SEIMBANG MAHASISWA PROGRAM STUDI PENDIDIKAN DOKTER ANGKATAN 2013 FAKULTAS KEDOKTERAN UNIVERSITAS SAM RATULANGI - Maharibe, Christan C. (Universitas Sam Ratulangi, 2014)
Abstract: Nutrition knowledge affects oneâ€™s attitudes and behavior in the selection of food and will further affect the nutritional state of the individual concerned. This study aims to know the association between balanced nutrient knowledge and balanced nutrient practice amongst the 2013 Medical Students of General Medicine Study Program, University of Sam Ratulangi Manado.This study was an analytical cross sectional design, conduct in September â€“ December 2013 with 252 respondents. The data was collected primary data and secondary data, namely by distributing questionnaires to the respondents. Primary data including formation about knowledge and practice of the student obtained from the questionnaires. Secondary data about the general state of Medical Faculty of Sam Ratulangi University, Manado. The results showed that the level of knowledge of student about balanced nutrient, good knowledge of the 199 people (79%) and lack of knowledge of 53 people (21%). As for balanced nutrient practice of the students, good categories of 154 people (61.1%) and not good categories of 98 people (38.9%). Conclusion: Using the Chi Square test, the result showed that there was no significant relationship between balanced nutrient knowledge and balanced nutrient practice amongst the 2013 medical students of General Medicine study program, university of Sam Ratulangi, Manado (X2 = 0.026 and Ï = 0.871). Keywords: balanced nutrient knowledge, balanced nutrient practice Abstrak: Pengetahuan gizi seseorang berpengaruh terhadap sikap dan perilaku dalam memilih makanan dan selanjutnya akan berpengaruh pada keadaan gizi individu yang bersangkutan. Penelitian ini bertujuan untuk mengetahui hubungan pengetahuan gizi seimbang dengan praktik gizi seimbang mahasiswa Program Studi Pendidikan Dokter angkatan 2013 Fakultas Kedokteran Universitas Sam Ratulangi Manado. Desain penelitian ini bersifat analitik dengan pendekatan cross sectional dengan jumlah sampel sebanyak 252 orang. Pengumpulan data dilakukan dengan data primer dan data sekunder yaitu dengan cara membagikan kuesioner kepada responden. Data primer meliputi informasi tentang pengetahuan dan praktik mahasiswa diperoleh melalui kuesioner. Data sekunder meliputi keadaan umum Fakultas Kedokteran Universitas Sam Ratulangi Manado. Hasil penelitian menunjukkan bahwa pengeetahuan gizi seimbang mahasiswa sebagian besar baik yaitu sebanyak 199 orang (79%).dan pengetahuan gizi kurang 53 orang (21%). Adapun praktik gizi seimbang, kategori baik sebanyak 154 orang (61,1%) dan kategori tidak baik 98 orang (38,9%). Kesimpulan: Hasil penelitian menggunakan Chi Square dengan nilai uji Ï = 0,871 > 0,05 dengan nilai X2 = 0,026 menunjukkan tidak ada hubungan yang bermakna antara pengetahuan gizi seimbang dengan praktik gizi seimbang mahasiswa Program Studi Pendidikan Dokter angkatan 2013 Fakultas Kedokteran Universitas Sam Ratulangi Manado. Kata Kunci : Pengetahuan gizi seimbang, praktik gizi seimbang